The Hidden Population of AM CVn Binaries in the Sloan Digital Sky Survey - P. J. Carter; T. R. Marsh; D. Steeghs; E. Breedt; C. M. Copperwheat; B. T. Gansicke; P. J. Groot; G. Nelemans (Acta Polytechnica CTU Proceedings)
We present results from a spectroscopic survey designed to uncover AM Canum Venaticorum (AM CVn) binaries hidden in the photometric database of the Sloan Digital Sky Survey (SDSS). The discovery of only 7 new AM CVns in the observed part of our sample suggests a lower space density than previously predicted. Based on the complete g≤19 sample, we calculate an observed space density for AM CVns of (5 ± 3) × 10−7 pc−3. We also compare the cataclysmic variables (CVs) discovered via this survey to those found in the SDSS spectroscopy, and we discuss SBSS 1108+574, an unusually helium-rich CV that has a spectroscopically confirmed orbital period of 55 minutes, well below the CV period minimum (~80 min). SBSS 1108+574 may represent an AM CVn forming via the ‘evolved CV’ formation channel.